Determine Hospital Management Priority Strategies from the Results of Measuring Hospital Readiness in Indonesia - Wati Mekarsari; Dumilah Ayuningtyas (Ridwan Institute, 2023)
WHO publishes an interim guideline on the Rapid Hospital Readiness Checklist. Countries can use the guidelines to help determine hospital capacity in response to the COVID-19 pandemic and identify gaps and key areas that require development/investment actions to maintain hospital quality. This study is to analyze the readiness of hospitals in Indonesia from the results of filling out the Hospital Readiness Checklist uploaded on the mutufasyankes.kemkes.go.id application of the Indonesian Ministry of Health. This study used a quantitative approach by utilizing secondary data taken by researchers from the application. The Rapid Hospital Readiness Checklist consists of 12 components that can be measured as a percentage achievement of each component. Data collection from the mutufasyankes.kemkes.go.id application was obtained by a total of 618 hospitals from 3081 registered hospitals in Indonesia that filled and uploaded on the application until April 30, 2023. A total of 618 hospitals reported Hospital Readiness from 12 existing components, the average achievement per component of 618 hospitals was 88%. The 12th component (Infection Prevention and Control Component) has the highest percentage (94%) and the 10th component (Occupational Health, Mental Health and Psychosocial Support Component has the lowest percentage (77%). Looking at the average results of the profit web picture as a visual illustration of Hospital Readiness measurements in 618 hospitals in Indonesia, it is said that hospitals in Indonesia in terms of the Infection Prevention and Control component are said to be good and for the components of Occupational Health, Mental Health and Psychosocial Support from hospitals need to be followed up again. So that the condition of hospitals in Indonesia at the lowest component of Hospital Readiness during the pandemic can be said to be unprepared. Therefore, the results of Hospital Readiness measurements in Indonesia can be used to determine priority strategies for hospital management by maximizing the Hospital Occupational Health and Safety (K3RS) program so that healthy Indonesian health workers are realized.